Distribution of Recessive Genetic Defect Carriers in Holstein Friesian Cattle: A Polish Perspective - Marta Gozdek; Sebastian Mucha; Adam Prostek; Dariusz Kamola; Tomasz Sadkowski (Animals)
Genetic disorders are caused by a hereditary change in the structure of DNA that may hurt the health and life of animals. Several recessive haplotypes and a few causative mutations are known in Holstein Friesian cattle: CDH (Holstein cholesterol deficiency), haplotypes with a homozygous deficiency in Holstein (HH1, HH3, HH4, HH5, HH6, HH7), BLAD (bovine leukocyte adhesion deficiency), DUMPS (deficiency of uridine monophosphate synthase), FXI (factor XI deficiency), HHM (mule foot, syndactyly), and BC (citrullinaemia). From a breeding point of view, these genetic diseases have highly negative effects and are a significant problem for breeders, exposing them to economic losses and hurting animal welfare. This study aimed to characterize the Polish population of Holstein Friesian dairy cattle, considering the carrier status of twelve selected genetic defects. This study was based on genotype data collected from 78,884 cows and 691 bulls of the Holstein Friesian variety. The studies were performed using Illumina Infinium microarrays. Among both bulls and cows, the highest numbers of carriers were detected for HH5 (appropriately 6.7% and 5.4%). The lowest numbers of carriers were detected for DUMPS, factor XI, and HHM. The study revealed one calf suffering from cholesterol deficiency.